Medical And Biological Aspects Of Women’s Sports (Global Scientific Review, 2024)
The article is dedicated to study of problems of women’s sport. In this work we have considered an affect of physical exercises on a woman organism in traditional and “nontraditional” kinds of sport. There are stated biological differences in nature of men and women which should be taken info account at making choice of specialization and differentiated structure of training loadings according to regime of trainings.